Human aggression and violence : causes, manifestations, and consequences - 4 0 16; Shaver, Phillip R.;Mikulincer, Mario; 5 (Washington, DC : American Psychological Association, 2011)
This book provides an impressive, well-rounded, authoritative overview of the latest research and theory about human aggression. Written by a diverse phalanx of highly respected experts, from evolutionary psychologists and behavioral geneticists to developmental, social, and clinical psychologists, the chapters offer a rich assortment of perspectives and an indispensable survey of issues, facts, and theories about why and how people hurt each other. It is an ideal introduction to the modern psychology of aggression for scholars and students, and a convenient reference for specialists, journalists, and the general public.-Roy F. Baumeister, author of Evil: Inside Human Violence and Cruelty This volume is an outstanding, integrated, biopsychosocial approach to aggression ranging over the contributions of genes, neurophysiology, early life influences, social relationships, personality, and cultures and exploring the victim perspective. Edited by internationally renowned researchers in attachment and social relationships, this gem of a book provides detailed, up-to-date access to current work by world leaders in the field. The best way of dealing aggression and becoming more compassionate is to better understand the facilitators and inhibitors of aggression, and this volume significantly contributes to this important endeavor.Paul Gilbert, author of The Compassionate Mind In this exciting book, leading experts cover contemporary theory, research, and practice in the psychology of aggression and violence. There is something here for everyone interested in these topics: basic theory, up-to-date reviews, and practical applications. There is a broad range of approachesincluding evolutionary background, neuroscience and genetics, environmental influences, violence between groups, and the impact on victims.John Archer, School of Psychology University of Central Lancashire, Lancashire, United Kingdom Violence and aggression have existed as long, as humankind, and the need to understand and control these forces has only continued to grow throughout history. Thanks to the advance of psychological research within the social and behavioral sciences, as well as several other scientific disciplines, we have more knowledge than ever before about the genetic, developmental, interpersonal, and cultural causes of aggression. Yet these findings have not been integrated into meaningful discussions about how to transform aggression research into practical applications. With so many answers to the question What makes a person violent? there is surprisingly little insight into How do we prevent violence? In this comprehensive book, editors Phillip R. Shaver and Mario Mikulincer have assembled chapters from international experts to provide a broad-based and multidisciplinary analysis of aggression and violence, their negative consequences, and promising interventions. Five sections examine major theoretical perspectives, genetic and environmental determinants, and the psychological and relational processes underlying human violence and aggression. The tone of the book is realistic in its investigation of violence as an inherent part of human genetics and interaction, but hopeful in its exploration of research-based interventions aimed at reducing violence in future generations. In its assessment of aggression and violence across individual, relational and societal levels, this book will engage a broad audience. This book is part of the Herzliya Series on Personality and Social Psychology. Phillip R. Shaver, PhD,, a social and personality psychologist, is Distinguished Professor of Psychology at the University of California, Davis. Before moving there, he served on the faculties of Columbia University, New York University, University of Denver, and State University of New York at Buffalo. He has coauthored and co-edited numerous books. He is a member of the editorial boards of Attachment and Human Development, Personal Rela.
The general aggression model / C. Nathan DeWall and Craig A. Anderson -- Ip3s theory : instigating, impelling, and inhibiting factors in aggression / Erica B. Slotter and Eli J. Finkel -- Applying adaptationism to human anger : the recalibrational theory / Aaron Sell -- A behavioral-systems perspective on human aggression / Phillip R. Shaver, Michal Segev, and Mario Mikulincer -- Dispositional influences on human aggression / Jennifer L. Tackett and Robert F. Krueger -- A social neuroscience perspective on the neurobiological bases of aggression / Thomas F. Denson -- The transmission of aggressiveness across generations : biological, contextual, and social learning processes / L. Rowell Huesmann, Eric F. Dubow, and Paul Boxer -- Genetic and environmental influences on aggression / Soo Hyun Rhee and Irwin D. Waldman -- Social information processing patterns as mediators of the interaction between genetic factors and life experiences in the development of aggressive behavior / Kenneth A. Dodge -- Violence and character : a CuPS (culture x person x situation) perspective / Dov Cohen and Angela K.-y. Leung -- Mirror mirror on the wall, who's the most aggressive of them all? : narcissism, self-esteem, and aggression / Sander Thomaes and Brad J. Bushman -- Evolved mechanisms for revenge and forgiveness / Michael McCullough, Robert Kurzban, and Benjamin A. Tabak -- Attachment, anger, and aggression / Mario Mikulincer and Phillip R. Shaver -- Attachment and violence : an anger born of fear / Donald G. Dutton -- To respect and being respected can reduce aggression in parent-child relations and in schools / Ofra Mayseless and Miri Scharf -- An existential perspective on violent solutions to ethno-political conflict / Gilad Hirschberger and Tom Pyszczynski -- The emotional roots of intergroup aggression : the distinct roles of anger and hatred / Eran Halperin -- Tension and harmony in intergroup relations / Tamar Saguy ... [et al.] -- Influence of violence and aggression on children's psychological development : trauma, attachment, and memory / Sheree L. Toth ... [et al.] -- The paradox of partner aggression : being committed to an aggressive partner / Ximena B. Arriaga and Nicole M. Capezza -- The psychological toll of exposure to political violence : the Israeli experience / Zahava Solomon and Karni Ginzburg.
Series statement from jacket flap.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Aggressiveness.;Violence. -- 20; 20; 2